2014
DOI: 10.1051/matecconf/20141303003
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Attenuation of Plate Using Multiple Vibration Absorbers

Abstract: Abstract. Vibrations are undesired phenomenon and it can cause harm, distress and unsettling influence to the systems or structures, for example, aircraft, automobile, machinery and building. One of the approach to limit this vibration by introducing passive vibration absorber attached to the structure. In this paper, the adequacy of utilizing passive vibration absorbers are investigated. The vibration absorber system is designed to minimize the vibration of a thin plate fixed along edges. The plate's vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…3a-d, it was concluded that four absorbers attachment is more effective to reduce the vibration amplitude of a beam. This result thus corroborated well with our previous findings [3,4]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3a-d, it was concluded that four absorbers attachment is more effective to reduce the vibration amplitude of a beam. This result thus corroborated well with our previous findings [3,4]. …”
Section: Resultssupporting
confidence: 93%
“…Apparently with adding vibration absorbers, the vibration amplitude of beam reduces significantly, although the result of without attached absorber was not shown in the manuscript. This is because it has been proved in our previous study [2][3][4], that the addition of absorber can minimize the vibration amplitude. From Figs.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Again it shows that the theoretical equation plotted by Matlab® is almost identical with numerical of Ansys®. It is found that by adding SMD to a beam has significantly reduce the displacement amplitude about 30% and this was agreed with our previous findings [16][17][18][19][20]. Thus indicates that the derivation of mathematical equation of a simply supported beam with attached SMD was successful.…”
Section: Resultssupporting
confidence: 90%
“…Assuming the Young's modulus E, cross sectional area A, area moment of inertia I and density ρ are constant along the beam length L, the equation of motion for a simplysupported beam can be expressed by [20]: …”
Section: Fig 2 Schematic Of a Simply Supported Beammentioning
confidence: 99%